Pengaruh Program Kampus Mengajar dalam Meningkatkan Kemampuan Literasi dan Numerasi Peserta Didik Kelas V UPT SPF SD Negeri Maricaya 2: The Effect of the Teaching Campus Program in Improving Literacy and Numeracy Skills of Grade V Students of UPT SPF SD Negeri Maricaya 2 - Audiba Tungga Dewi; Sugeng A. karim; Nurul Mukhlisah Abdal (Sakura Digital Nusantara, 2025)
Low levels of literacy and numeracy among students remain a critical challenge in the education sector, as both skills are essential for developing critical thinking and mastering learning materials. As an effort to address this issue, the Kampus Mengajar (Teaching Campus) program was launched to improve the quality of teaching and learning in schools. This study aims to examine: (1) the effect of the Kampus Mengajar program on students’ literacy skills; and (2) its effect on students’ numeracy skills. A quantitative approach was employed using a pre-experimental design (one-group pretest–posttest) involving 25 fifth-grade students as a saturated sample. Data were collected through pretests and posttests, then analyzed using descriptive statistics and hypothesis testing. The results indicate that (1) the Kampus Mengajar program had a significant effect on improving students’ literacy skills (sig = 0.000 < 0.05); and (2) it also had a significant effect on enhancing students’ numeracy skills (sig = 0.000 < 0.05). These findings suggest that the Kampus Mengajar program plays an important role in enhancing students' literacy and numeracy competencies.